Rapid Enzymatic Response to Compensate UV Radiation in Copepods - Souza, María Sol (2012)
Ultraviolet radiation (UVR) causes physical damage to DNA, carboxylation of proteins and peroxidation of lipids in copepod crustaceans, ubiquitous and abundant secondary producers in most aquatic ecosystems. Copepod adaptations for long duration exposures include changes in behaviour, changes in pigmentation and ultimately changes in morphology. Adaptations to short-term exposures are little studied. Here we show that short-duration exposure to UVR causes the freshwater calanoid copepod, Eudiaptomus gracilis, to rapidly activate production of enzymes that prevent widespread collateral peroxidation (glutathione S-transferase, GST), that regulate apoptosis cell death (Caspase-3, Casp-3), and that facilitate neurotransmissions (cholinesterase-ChE). None of these enzyme systems is alone sufficient, but they act in concert to reduce the stress level of the organism. The interplay among enzymatic responses provides useful information on how organisms respond to environmental stressors acting on short time scales.